J justme1604 New member Joined Oct 29, 2019 Messages 4 Nov 4, 2019 #1 Can someone please explain step by step how the answer is B. Thank you.

S Subhotosh Khan Super Moderator Staff member Joined Jun 18, 2007 Messages 20,882 Nov 4, 2019 #2 justme1604 said: View attachment 14467 Can someone please explain step by step how the answer is B. Thank you. Click to expand... I'll do example for you - then you do the rest. The first empty box (bottom-left) - you need to fill in the value of "y" using the function when you are given x = -8 y + 3 = -(1/2) * (x + 4) y + 3 = -(1/2) * (-8 + 4) y + 3 = -(1/2) * (- 4) y + 3 = (4/2) y + 3 = 2 y + 3 - 3 = 2 - 3 y = -1 Now you calculate the rest. If you get stuck - write back including your work and point out exactly where you are stuck!

justme1604 said: View attachment 14467 Can someone please explain step by step how the answer is B. Thank you. Click to expand... I'll do example for you - then you do the rest. The first empty box (bottom-left) - you need to fill in the value of "y" using the function when you are given x = -8 y + 3 = -(1/2) * (x + 4) y + 3 = -(1/2) * (-8 + 4) y + 3 = -(1/2) * (- 4) y + 3 = (4/2) y + 3 = 2 y + 3 - 3 = 2 - 3 y = -1 Now you calculate the rest. If you get stuck - write back including your work and point out exactly where you are stuck!